(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2009)
The chemical and physical analysis of Diamond, Pure Chem, Dangote and Elephant cements in Nigerian market have been carried out by analysis of metal oxides (A12O3, SiO2, CaO, etc.), physical characteristics of the samples (setting time, loss on ignition, insoluble residue, specific surface area, etc.) and important factors for predicting effectiveness of the cement samples.The mean value of CaO, SiO2, K2O, and A12O3 were 61.45 ± 0.22 and 5.57 ± 0.38 with percentage coefficient of variance as 2.15, 0.92, 53.66 and 6.82, respectively. Dangote had the least CaO (59.60%), insoluble residue (4.70) and setting time (195 sec) while pure chem had the highest specific surface area of 412 m2/kg with Diamond having the least percentage loss on ignition of 5.50. The mean values for time saturation factor, silica ratio, free lime and alumina ratio were 90.10 ± 3.02, 2.23 ± 0.10, 169.00 ± 0.13 and ± 0.79 respectively. The coefficient of variation suggests that there were no significant differences between all these factors except free lime. Pure chem has a free lime value of 2.28 which is highly significance compared with others. An empirical equation has been suggested to predict the variation of the compressive strength against time, which agrees very well with the experimental results. Key words: Cement, Diamond, Dangote, Metal oxide, Pure Chem and Quality paramaters. doi: 10.3329/bjsir.v44i1.2712 Bangladesh J. Sci. Ind. Res. 44(1), 41-50, 2009